Mapping the patchy legislative landscape of non-native tree species in Europe. (3rd June 2020) - Pötzelsberger, Elisabeth; Lapin, Katharina; Brundu, Giuseppe; Adriaens, Tim; Andonovski, Vlatko; Andrašev, Siniša; Bastien, Jean-Charles; Brus, Robert; Čurović, Milić; Čurović, Željka; Cvjetković, Branislav; Đodan, Martina; et al.
Abstract: Europe has a history rich in examples of successful and problematic introductions of trees with a native origin outside of Europe (non-native trees, NNT). Many international legal frameworks such as treaties and conventions and also the European Union have responded to the global concern about potential negative impacts of NNT that may become invasive in natural ecosystems. It is, however, national and regional legislation in particular that affects current and future management decisions in the forest sector and shapes the landscapes of Europe. We identified all relevant legal instruments regulating NNT, the different legal approaches and the regulatory intensity in 40 European countries (no microstates). Information on hard and effective soft law instruments were collected by means of a targeted questionnaire and consultation of international and national legislation information systems and databases. In total, 335 relevant legal instruments were in place in June/July 2019 to regulate the use of NNT in the investigated 116 geopolitical legal units (countries as well as sub-national regions with their own legislation). Countries and regions were empirically categorized according to ad hoc -defined legislation indicators. These indicators pay respect to the general bans on the introduction of non-native species, the generally allowed and prohibited NNT, approval mechanisms and specific areas or cases where NNT are restricted or prohibited. Our study revealed a very diverse landscape of legal frameworks across Europe, with a large variety of approaches to regulating NNT being pursued and the intensity of restriction ranging from very few restrictions on species choice and plantation surface area to the complete banning of NNT from forests. The main conclusion is that there is a clear need for more co-ordinated, science-based policies both at the local and international levels to enhance the advantages of NNT and mitigate potential negative effects.